2004
DOI: 10.2337/diacare.27.11.2581
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hospitalizations and Death Associated With Influenza Vaccination Among Patients With and Without Diabetes

Abstract: OBJECTIVE -To assess whether the influenza vaccination of community-dwelling, diabetic, elderly individuals is associated with reduced rates of hospitalization and death.RESEARCH DESIGN AND METHODS -In this outcome-research study, we compared mortality and hospitalization rates of 15,556 patients aged Ն65 years followed using a diabetes registry in a large health maintenance organization to that of 69,097 members not suffering from chronic disease who were considered as a reference group. The study outcomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 10 publications
1
35
0
3
Order By: Relevance
“…In the present study, with good matching of the vaccine, a vaccine effectiveness estimate of 39% (though not significant) compares with the U.S. study (11). Heymann et al (12) did not find an additional benefit in patients with diabetes, but the study could be discussed because of the low influenza activity during the study season.…”
Section: Conclusion -O U R S T U D Y Clearly Demonstrates Substantiamentioning
confidence: 62%
See 1 more Smart Citation
“…In the present study, with good matching of the vaccine, a vaccine effectiveness estimate of 39% (though not significant) compares with the U.S. study (11). Heymann et al (12) did not find an additional benefit in patients with diabetes, but the study could be discussed because of the low influenza activity during the study season.…”
Section: Conclusion -O U R S T U D Y Clearly Demonstrates Substantiamentioning
confidence: 62%
“…Hak et al (11) also found significant vaccine effectiveness among the subgroup of elderly individuals with diabetes with reductions in hospitalization for influenza or pneumonia or death from any cause ranging from 50% in one influenza season to 21% in the second season. In contrast, Heymann et al (12) did not find clinical effects of such vaccination in the subgroup of elderly individuals with diabetes.…”
mentioning
confidence: 90%
“…Diabetes is associated with impaired T cell function and disorders of humoral immunity (15). To our knowledge, only seven studies have been published regarding the immunogenicity of influenza vaccination among diabetic patients (6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…To lessen tumor drug resistance for better restorative adequacy, blend chemotherapy has for some time been embraced in clinics as an essential cancer treatment regimen. Fullerene C 60 (FnC 60 ) is a nanoparticle that comprises of 32 confronts, which incorporate 12 pentagons and 20 hexagons, and the carbon particles are organized at 60 vertices of truncated icosahedrons (Heymann et al 2004). The natural impacts of FnC 60 have been the subject of extraordinary examination over the previous decade, and it has indicated advantageous activity as a neuroprotectant and in addition an anticancer, mitigating, antiatherogenic and radio defensive operator (Tykhomyrov et al 2008).…”
Section: Page 2 Of 32mentioning
confidence: 99%